Hormone therapy use and physical quality of life in postmenopausal women with multiple sclerosis. (4th October 2016) - Bove, Riley; White, Charles C.; Fitzgerald, Kathryn C.; Chitnis, Tanuja; Chibnik, Lori; Ascherio, Alberto; Munger, Kassandra L.
Abstract : Objective: To determine the association between hormone therapy (HT) and physical quality of life (QOL) in postmenopausal women with multiple sclerosis (MS). Methods: We included female participants from the prospective Nurses' Health Study, with a diagnosis of definite or probable MS, who had completed a physical functioning assessment (PF10; subscale of the 36-Item Short-Form Health Survey QOL survey) at a time point between 3 and 10 years after their final menstrual period (early postmenopause). We assessed the association between HT use at this time point (never vs at least 12 months of systemic estrogen with/without progestin) and both PF10 and the 36-Item Short-Form Health Survey Physical Component Scale. We used a linear regression model adjusting for age, MS duration, menopause type and duration, and further for additional covariates (only ancestry was significant). Results: Among 95 participants meeting all inclusion criteria at their first postmenopausal assessment, 61 reported HT use and 34 reported none. HT users differed from non–HT users in MS duration ( p = 0.02) and menopause type ( p = 0.01) but no other clinical or demographic characteristics. HT users had average PF10 scores that were 23 points higher than non–HT users (adjusted p = 0.004) and average Physical Component Scale scores that were 9.1 points higher in the 59 women with these available (adjusted p = 0.02). Longer duration of HT use was also associated with higher PF10 scores ( p = 0.02, adjusted p = 0.06). Conclusions: Systemic HT use was associated with better physical QOL in postmenopausal women with MS in this observational study. Further studies are necessary to investigate causality.